Close correlation between urinary sodium excretion and response to tolvaptan in liver cirrhosis patients with ascites. Issue 3 (19th May 2016) - Uojima, Haruki; Kinbara, Takeshi; Hidaka, Hisashi; Sung, Ji Hyun; Ichida, Masachika; Tokoro, Shinnosuke; Masuda, Sakue; Takizawa, Satoshi; Sasaki, Akiko; Koizumi, Kazuya; Egashira, Hideto; Kako, Makoto
Abstract : Aim : To assess the correlation between response to tolvaptan and treatment‐related factors in liver cirrhosis patients. Methods : This single‐center retrospective study was carried out at Shonan Kamakura General Hospital in Kanagawa, Japan, between October 2013 and September 2015. Forty‐three liver cirrhosis patients (mean age, 65.7 years) with insufficient responses to conventional diuretics for at least 7 days were enrolled. All patients received oral tolvaptan (7.5 mg/day for 7 days) and guideline‐directed medical therapy including sodium intake restrictions. A responder to tolvaptan was defined as a patient having a ≥2‐kg decrease in body weight 1 week after commencing drug treatment, and a non‐responder was defined as a patient not losing ≥2 kg in body weight 1 week after commencing treatment. We investigated the correlation of change in body weight for 1 week after drug administration compared to baseline clinical characteristics. Results : The mean body weight change from the baseline on the final dosing day was −2.47 ± 3.34 kg ( P  < 0.0001). There were 20 (46.5%) responders to tolvaptan. Urinary sodium and volume excretion was higher in responders than in non‐responders (108.2 ± 70.5 vs 42.6 ± 36.7, P  = 0.0003; 1462.8 ± 625.7 vs 960.9 ± 600.6, P  = 0.0073). Logistic regression analyses for responders to tolvaptan were carried out, and independent correlation of the responders was urinary sodium excretion ( P  = 0.0114; hazard ratio, 0.9418; 95% confidence interval, 0.8768−0.9896) in the multivariate analyses. Conclusion : In decompensated liver cirrhosis patients, urinary excretion sodium showed good correlation with tolvaptan response.